Retrospective Comparative Study of the Short and Long Term Outcomes of Percutaneous Coronary Intervention and Coronary Artery Bypass Graft in Chronic Kidney Disease Population - WAAGN, Nishanthi; Chula, Herath; Sithum, Manjika (Cardiology and Cardiovascular Medicine, 2022)
Introduction: Patients with chronic kidney disease are at increased risk of cardiovascular disease and death. For patients with Chronic Kidney Disease (CKD) and multivessel Coronary Artery Disease (CAD), the optimal revascularization study is still debatable. This is a single center retrospective study to compare the short- and long-term outcomes of Percutaneous Coronary Intervention (PCI) and Coronary Artery Bypass Graft (CABG) in CKD patients who presented with acute coronary syndrome. in Sri Lanka. Objectives: This study was aimed to describe the sociodemographic distribution of the population with CKD and acute coronary syndrome, to compare the baseline characteristics with outcomes include recurrence of ACS and LV(left ventricular dysfunction) and to compare the short and long term outcomes of PCI and CABG in CKD population. Methodology: A retrospective comparative study was conducted at Sri Jayewardenepura General Hospital on patients with CKD who underwent CABG and PCI since 2013 to 2017. Data were obtained from past medical records, clinic records and telephone interviews. The outcomes of the patients with CKD who underwent PCI were matched to patients who underwent CABG for multivessel disease by using univariate and multivariate statistical analysis methods. The outcomes include deaths, recurrence of acute coronary syndrome, left ventricular LV dysfunction, bleeding complications and stroke. Results: There were 423 patients met inclusion criteria with mean age 59.94 ± 8.381 years. There were 81.3%(n=344) of males. The prevalence of Diabetes, hypertension, dyslipidemia in the study sample was 89.2%(n=363),83.3%(n=339), and 34.9%(n=142) respectively. The prevalence of CKD stage I, II ,111,1V and V was 1.4%(n=6) ,38% (n=165), 36.9% (n=156),12.5% (